HUBUNGAN PELAKSANAAN TUGAS KELUARGA DALAM BIDANG KESEHATAN DENGAN FREKUENSI KEKAMBUHAN PASIEN SKIZOFRENIA DI IGD RSJ SAMBANG LIHUM - Syafwani, Muhammad (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
The factor that causes recurrence of schizophrenic patients is the lack of implementation of family duties in caring for family members who suffer from the disease. The family is the person or closest environment of the person with schizophrenia because there is a burden on the family to care for a family member who has schizophrenia resulting in the family not caring about and misbehaving with the patient. Treatment of schizophrenic patients requires emotional stability and family support, thus carrying out family duties is needed to care for schizophrenic patients. Objective The study aims to determine the relationship between the implementation of family tasks in the health sector and the frequency of recurrence of schizophrenic patients in the Emergency Room of the Sambang Lihum Hospital. Analytical research design with cross sectional. The sample is 89 respondents with Accidental Sampling Technique. Questionnaire research instrument. Statistical test using the Spearman Rank Correlation with a degree of significance α = 0.05. this study showed that there was a significant relationship between the implementation of family tasks in the health sector and the frequency of recurrence of schizophrenia patients (P value = 0.000). In addition, the results of statistical analysis also obtained a correlation value of -0.651, which means that there is a strong relationship with the direction of a negative relationship, meaning that the higher the family assignment in the health sector, the lower the frequency of recurrence in schizophrenic patients and vice versa.